Eye movements and postural control in dyslexic children performing different visual tasks - Razuk, Milena; Barela, Jose Angelo [UNESP]; Peyre, Hugo; Gerard, Christophe Loic; Bucci, Maria Pia (Public Library Science, 2018)
The aim of this study was to examine eye movements and postural control performance among dyslexic children while reading a text and performing the Landolt reading task. Fifteen dyslexic and 15 non-dyslexic children were asked to stand upright while performing two experimental visual tasks: text reading and Landolt reading. In the text reading task, children were asked to silently read a text displayed on a monitor, while in the Landolt reading task, the letters in the text were replaced by closed circles and Landolt rings, and children were asked to scan each circle/ring in a reading-like fashion, from left to right, and to count the number of Landolt rings. Eye movements (Mobile T2 (R), SuriCog) and center of pressure excursions (Framiral (R), Grasse, France) were recorded. Visual performance variables were total reading time, mean duration of fixation, number of pro- and retro-saccades, and amplitude of pro-saccades. Postural performance variable was the center of pressure area. The results showed that dyslexic children spent more time reading the text and had a longer duration of fixation than non-dyslexic children. However, no difference was observed between dyslexic and non-dyslexic children in the Landolt reading task. Dyslexic children performed a higher number of pro- and retro-saccades than non-dyslexic children in both text reading and Landolt reading tasks. Dyslexic children had smaller pro-saccade amplitude than non-dyslexic children in the text reading task. Finally, postural performance was poorer in dyslexic children than in non-dyslexic children. Reading difficulties in dyslexic children are related to eye movement strategies required to scan and obtain lexical and semantic meaning. However, postural control performance, which was poor in dyslexic children, is not related to lexical and semantic reading requirements and might not also be related to different eye movement behavior.